1985
DOI: 10.1099/0022-1317-66-4-797
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Antigenic Variations among Geographical Isolates of Sindbis Virus

Abstract: SUMMARYThe genetic and antigenic variation in 12 Sindbis (SIN) virus isolates from four zoogeographic regions (Paleoarctic, Ethiopian, Oriental and Australian) has been examined at a molecular level. RNase T1 oligonucleotide fingerprinting of genomic RNA from SIN isolates revealed that the primary structure of the RNA from viruses from each zoogeographic region was unique. The E1 and E2 glycoproteins and the capsid protein of two isolates from each zoogeographic region were compared by tryptic peptide mapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
(30 reference statements)
1
21
0
Order By: Relevance
“…The results confirm earlier reports that significant genetic diversity exists between isolates of SIN virus from the Paleoarctic\Ethiopian and Oriental\Australian zoogeographic regions (Norder et al, 1996 ;Olson & Trent, 1985 ;Rentier-HEF Delrue & Young, 1980). The isolates contained within each of the two genotypes were closely related genetically.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The results confirm earlier reports that significant genetic diversity exists between isolates of SIN virus from the Paleoarctic\Ethiopian and Oriental\Australian zoogeographic regions (Norder et al, 1996 ;Olson & Trent, 1985 ;Rentier-HEF Delrue & Young, 1980). The isolates contained within each of the two genotypes were closely related genetically.…”
Section: Discussionsupporting
confidence: 81%
“…Rentier-Delrue & Young (1980) and Olson & Trent (1985), using a different Malaysian isolate of SIN virus, have also demonstrated that the Malaysian isolate was more closely related to Australian isolates than to other isolates from the Oriental zoogeographic region. The Oriental and Australasian zoogeographic regions are separated by the Wallace Line in the Indo-Australian archipelago, and seroepidemiological studies have indicated that the alphavirus Chikungunya virus and the flavivirus Japanese encephalitis (JE) virus may be restricted to the Oriental zoogeographic region, whereas the alphavirus RR virus and flavivirus Murray Valley encephalitis (MVE) virus are restricted to the Australian zoogeographic region (Mackenzie et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alphaviruses and other arthropod-borne viruses also appear to undergo lower rates of evolution than many other animal RNA viruses that replicate solely in vertebrates (6,33,35). Rates of SINV nucleotide substitution, deduced from oligonucleotide fingerprinting, are approximately 4 ϫ 10 Ϫ4 substitutions per nucleotide per year (18,36), similar to estimates for other alphaviruses and other arboviruses and approximately 10-fold lower than rates reported for many single-host RNA viruses (25).…”
mentioning
confidence: 70%